PENINGKATAN HASIL BELAJAR SISWA MENGGUNAKAN METODE PEMBELAJARANCOOPERATIVE LEARNING TIPECO-OP CO-OP DALAM PEMBELAJARAN IPSDI KELAS V SD - Susanti, Nia; Hamimah, Hamimah; Reinita, Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
The purpose of this study was to describe and increase in student learning outcomes in social studies learning by using the Co-op Co-op Cooperative Learning an Methode in the fifth grade of elementary school. Types of this research was classroom action research with qualitative and quantitative approach. The research subject was 29 grade V students consisting of 16 men and 13woman. The research procedure consistend of planning, implementing, observing, and reflecting. The result of the study showed and increase in aspects: a) RPP cycle I with an average of 71,42% and cycle II 92,85%, b) implementation on the aspect of the teacher cycle I with an average of 77,27% and the second cycle 95,45%, while for the implemenetation of aspect of the students of the first cycle with an average 74,99% and cycle II 93,18%, c) learning outcomes in the first cycle with an average of 71,76 and cycle II 86,18. The conclusions from the result of the research conducted are using the Co-op Co-opCooperative Learning anMethode improve student learning outcomes in social stundent learning in class V SDN 17 Bungo Pasang City of Padang